HUBUNGAN AKTIVITAS SEKSUAL PADA USIA DINI, PROMISKUITAS DAN BILAS VAGINA DENGAN KEJADIAN KANKER LEHER RAHIM PADA PASIEN ONKOLOGY DI RSUD Dr.MOEWARDI SURAKARTA - Ridhaningsih, .; Djannah, Sitti Nur (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2011)
Background: Cervical cancer ranks the top cause of cancer deaths in developing countries. At Dr. Moewardi Hospital Surakarta cervical cancer was found in most cancers. Risk factors associated with health and cleanliness of the female reproductive tract can increase the incidence of cervical cancer. Purpose this study aims to determine factors associated with female reproductive health tract and the occurrence of cervical cancer. Method: The study was a quantitative analytical research used cross sectional design. Data used primary data from interviews and secondary data from medical records. Bivariate analysis using chi square test used to prove the hypothesis. Results: Statistical analysis by chi square test for sex at an early age got p value=0,382 and the prevalence ratio= 1,375, for promiscuity with incidence cervical cancer got p value=0,481 and prevalence ratio=1,314, for vaginal douching with incidence cervical cancer got p value=0,121 and prevalence ratio=0,571. Conclusion: There was no significant correlation between sex on early age with incidence of cervical cancer, there was no significant correlation between promiscuity with incidence of cervical cancer, there was no significant correlation between vaginal douching with incidence of cervical cancer at Dr. Moewardi Hospital Surakarta on Mey until Juny 2010. Key words: sex at an early age, promiscuity, rinse the vagina, cervix cancer